The analgesic efficacy of continuous transversus abdominis plane block in renal transplant recipients - Beena Kandarp Parikh; V Waghmare; Veena R Shah; P Modi; S Rizvi; S Khemchandani; B Butala; G Parikh (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: Transversus abdominis plane (TAP) block is suitable for operations where parietal pain is a major cause of pain. Renal transplant recipients are ideally suited to gain maximum benefit from TAP block as the incision classically involves the lower abdomen. This study was conducted to evaluate the analgesic efficacy of continuous TAP block in transplant recipients. Material and Methods: In a prospective double-blind study, 40 chronic renal failure patients undergoing open renal transplant were randomly divided into two groups. At the end of surgery during closure, a multiorifice epidural catheter was placed in TAP plane. Study group (Group S) received Inj bupivacaine bolus 1 mg/kg (0.25%) followed by infusion 0.25 mg/kg (0.125%) through the catheter, whereas control group (Group C) received normal saline through the catheter. Inj pentazocine (0.3 mg/kg) was given as rescue analgesic at visual analogue score (VAS) > 3 in any group at rest or on movement. The analgesic efficacy was judged by VAS, time of first rescue analgesic, and total analgesic consumption in 24 h. Results: Patients in Group S had significant lower VAS scores, longer time to first rescue analgesic (270 ± 347.96 vs. 42.85 ± 32.27 min) and lower pentazocine consumption (9.75 ± 13.95 vs. 56.42 ± 12.46 mg) in 24 h. There was significant sedation in Group C. Conclusion: The TAP catheter technique for postoperative pain control after renal transplant has proved to be effective in relieving the postoperative pain after renal transplant with less pentazocine requirement and less sedation.